Observation of total ozone fields in the Antarctic atmosphere from TOVS of TIROS-N/NOAA - Yamanouchi, T.; Kawaguchi, S.; Iwashina, I.; Suzuki, K. (1985)
Total ozone amounts in the Antarctic atmosphere are derived from infrared nadir scanning data of TIROS Operational Vertical Sounder (TOVS) of NOAA-6 and 7. HRPT data of the TIROS-N NOAA series of meteorological satellites have been received at Syowa Station (69 deg 00'S, 39 deg 35'E), Antarctica, about once a day since February 1980, by the Japanese Antarctic Research Expedition. HIRS/2 data of TOVS were extracted from HRPT data after being converted into CCT at the home institute. Total ozone amounts were derived for the northeastern part of the Antarctic, for about 100 orbits in 1981 and 1982.